Loose Monetary Policy and Financial Instability - Grimm, Maximilian; Jordà, Òscar; Schularick, Moritz; Taylor, Alan M (Review of Economic Studies, 2026)
Do periods of persistently loose monetary policy increase financial fragility and the likelihood of a financial crisis? This is a central question for policymakers, yet the literature does not provide systematic empirical evidence about this link at the aggregate level. In this article, we fill this gap by analysing long-run historical data. We find that when the stance of monetary policy is accommodative over an extended period, the likelihood of financial turmoil in the medium term increases considerably. We investigate the causal pathways that lead to this result and argue that credit creation and asset price overheating are important intermediating channels.